Second law analysis of the 2D laminar flow of two-immiscible, incompressible viscous fluids in a channel - Kamisli, Fethi; Öztop, Hakan Fehmi (Springer, 2008)
The laminar and fully developed flows of two immiscible fluids confined in a thin slit of constant wall heat fluxes are analyzed in terms of entropy generations due to irreversibility of forced convection heat transfer. The governing equations are analytically derived using expressions for velocity distributions. The derived equation for the dimensionless entropy generation number is used to interpret the relative importance of frictions to conduction by varying irreversibility distribution ratio phi. It is found that the minimum entropy generation takes place at the dimensionless half transverse distance (xi) of 0.3 for values of phi higher than zero. The entropy generation near the plate increases more rapidly in fluid I than in fluid II as viscous dissipation effects becomes more important. The velocity profiles are found to be in agreement with the distributions of the dimensionless entropy generation number (N (S) ) for two-immiscible incompressible flows in the slit.
Keywords: Constant Wall Temperature; Convective Heat-Transfer; 2-Fluid Porous Flow; Entropy Generation; Duct